Shadows of Pecan Hollow : a novel - Frost, Caroline (William Morrow, an imprint of HarperCollinsPublishers, 2022)
"It was 1970 when thirteen-year-old runaway Kit Walker was abducted by Manny Romero, a smooth-talking, low-level criminal, who first coddled her and then groomed her into his partner-in-crime. Before long, Kit and Manny were infamous for their string of gas station robberies throughout Texas, making a name for themselves as the Texaco Twosome. Twenty years after they meet, Kit has scraped together a life for herself and her daughter amongst the pecan trees and muddy creeks of the town of Pecan Hollow, far from Manny. But when he shows up at her doorstep a new man, fresh out of prison, Kit is forced to reckon with the shadows of her past, and her community is sent into a tailspin"--